CONTEMPORARY INFLATION DYNAMICS: DIAGNOSIS AND FACTOR ANALYSIS IN DEVELOPING COUNTRIES - Mohamed Aarab; Mariam Lazrak; Hamid El Amrani (Фінансово-кредитна діяльність: проблеми теорії та практики)
In an international context full of ambiguities, the developing economies are suffering more and more from the relentless increase in the general level of prices, which constitutes a disruptive factor in their macroeconomic equilibrium. The signs of crisis are starting to appear, and cyclical measures are no longer needed to readjust the parameters. Faced with this continuing trend in prices worldwide over the period 2018-2023, it seems essential to look behind the scenes and detail the underlying explanations behind this phenomenon. This article uses Morocco as an example to extract the determinants of inflation over the last decade, through a qualitative investigation of 30 observations. We use factor analysis (PCA) with Direct Oblimin Rotation, with a view to reducing the size of the data collected and deducing the real factors behind the new inflationary dynamic. The results obtained show that the rising inflation in Morocco is primarily driven by imported inflation affected by the COVID-19 pandemic and the Russian-Ukrainian war. Additionally, Internal factors such as economic freedom and the reform of the compensation fund influence in a second row the phenomenon analyzed.